Pengaruh Brand Experience dan Brand Passion Terhadap Brand Commitment Pada Pengguna Smartphone Iphone di Universitas Perjuangan - Kamil Abdul Hamid; Suci Putri Lestari; Dudu Risana (CV. ULIL ALBAB CORP, 2023)
This study aims to determine the effect of Brand Experience and Brand Passion on Brand Commitment (a survey of iPhone smartphone users at Perjuangan University). The method used in this study is causality through a survey approach. With a research sample of 100 Iphone Smartphone Users at the University of Perjuangan. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results of the study show that Brand Experience and Brand Passion have a significant influence on Brand Commitment in Iphone Smartphone Users at the University of Perjuangan. Partially, Brand Experience has a significant influence on Brand Commitment in Iphone Smartphone Users at Perjuangan University. Partially, Brand Passion has a significant influence on Brand Commitment in Iphone Smartphone Users at Perjuangan University